Authors’ Response - Branko Beronja; Aleksandra Karan; Biljana Lukic; Ivana Milosevic; Jelena Dotlic; Tatjana Gazibara (Monaldi Archives for Chest Disease)
Dear Editor, We read the comments by Rossato and Di Vincenzo with enthusiasm and appreciate their interest in our study, which helps deepen the discussion on smoking and COVID-19. Indeed, smoking is a major health issue worldwide, as it is associated with a variety of poor outcomes, including COVID-19...